Journalistic Framing of the Israel-Palestine Conflict: A Comparative Study of Western and Middle Eastern Media Perspectives - M Yoserizal Saragih (Dynamics Social : International Journal of Social Sciences and Communication, 2025)
This study analyzes the differences between Western and Middle Eastern media framing in reporting the Israeli-Palestinian conflict. Western media tends to portray Israel as a party threatened by terrorism, with a focus on national security. In contrast, Middle Eastern media highlight the suffering of the Palestinian people and criticize Israeli policies that are considered as occupation. By analyzing reports from media outlets such as BBC, CNN, Al Jazeera, and Al Arabiya, it was found that these framing differences influence global public opinion. Western countries are more supportive of a two-state solution with an emphasis on Israel's security, while Middle Eastern countries emphasize justice for Palestinians. This difference creates polarization that hinders the peace process and creates tension in international diplomacy. This research suggests the need for a more balanced and inclusive narrative to achieve a sustainable peace solution.